Visible tattoos in the service sector: a new challenge to recruitment and selection. (February 2015) - Timming, Andrew R
Drawing on 25 in-depth interviews with hiring managers and visibly tattooed respondents, this article explores the nature of prejudice surrounding body art in the service sector. It focuses on the impact of visible tattoos on employment chances. The study reveals a predominantly negative effect on selection, but the extent of employer prejudice is mitigated by: where the tattoo is located on the body; the organization or industry type; proximity of the role to customers; and the genre of the tattoo. Employer prejudice against tattoos is also driven largely by hiring managers' perceptions of consumer expectations regarding body art in the workplace.